Effects of sodium nitrate and OPC-GGBS concrete mix composition on phase transition of pore water at subzero temperatures - Kothari, Ankit; Hedlund, Hans; Illikainen, Mirja; Cwirzen, Andrzej (Construction and Building Materials, 2022)
Lowering the freezing temperature of the mixing water is crucial for concrete works at subzero temperatures. In this study, formation of ice was examined for various pastes and concretes of OPC-GGBS based, while exposed to a constant temperature of −15 °C. Sodium nitrate antifreeze admixture was added as 0, 6, 10, 15, 20, 25, 30 wt% by the total binder amount. The ice formation and its effects on the binder matrix microstructure was studied using differential scanning calorimetry (DSC), ultrasonic pulse velocity (UPV) and Scanning Electron Microscopy – Energy Dispersive Spectrometry (SEM-EDS). Several curing procedures were applied to samples before commencing tests. Results showed that, addition of 25 wt% of the sodium nitrate caused the most extensive delay of the ice growth. Mixes containing less admixture showed an increasing amount of the forming ice which in some cases lead to the development of the false strength. The hydration rate has been the highest for the mix with 25 wt% of the sodium nitrate and tended to be limited at lower additions. The porosity of the hydrated binder matrix tended to be lower for mixes characterized by a lower amount of the forming ice. In general, application of above freezing temperature resulted in resuming of the hydration process that led to densification of the microstructure and strength increase. This trend was more pronounced for mixes having lower amounts of the formed ice. Validerad;2022;Nivå 2;2022-03-03 (sofila) ARCTIC-ecocrete